A Function With Continuous Nonzero Derivative Whose Inverse Is Nowhere Continuous. Issue 5 (1st December 2016) - Lynch, Mark
Summary: A function with continuous nonzero derivative whose inverse is nowhere continuous is given. The function satisfies all the premises of the inverse function theorem except one: it is not defined on an open set.